2011
DOI: 10.1620/tjem.223.263
|View full text |Cite
|
Sign up to set email alerts
|

Association between High-Sensitivity C-Reactive Protein and Left Ventricular Diastolic Function Assessed by Echocardiography in Patients with Cardiovascular Risk Factors

Abstract: High-sensitivity C-reactive protein (hsCRP) has been demonstrated to play a causal role in atherosclerosis and to predict cardiovascular events in the general population. On the other hand, left ventricular (LV) hypertrophy and diastolic dysfunction assessed by echocardiography can also predict cardiovascular events in patients with cardiovascular risk factors. However, there are few data regarding the relationships among hsCRP, LV hypertrophy, and diastolic function. We examined the relationships among hsCRP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
(40 reference statements)
2
9
2
Order By: Relevance
“…In present study increased levels of CRP, was associated independently with Obesity, BMI, uncontrolled glicemia and uncontrolled BP. Results they are consistent with prior studies [27][28][29][30]. Another fact of great importance is the in luence of medication on several elektrocardiographic parameters, there are numerous drugs that cause prolongation and/or dispersion of repolarization.…”
Section: Discusionsupporting
confidence: 92%
See 1 more Smart Citation
“…In present study increased levels of CRP, was associated independently with Obesity, BMI, uncontrolled glicemia and uncontrolled BP. Results they are consistent with prior studies [27][28][29][30]. Another fact of great importance is the in luence of medication on several elektrocardiographic parameters, there are numerous drugs that cause prolongation and/or dispersion of repolarization.…”
Section: Discusionsupporting
confidence: 92%
“…Others have found similar results [25,26]. A number of previous studies have demonstrated that CRP levels correspond with individual components of MetS [27,28]. In present study increased levels of CRP, was associated independently with Obesity, BMI, uncontrolled glicemia and uncontrolled BP.…”
Section: Discusionsupporting
confidence: 87%
“…First, we did not take left atrial volume index [31] into account, for the assessment of diastolic dysfunction has been done in other studies [32][33][34]. Second, although atrial fibrillation may increase the risk of diastolic heart failure, we excluded such patients, as has been done in other studies [35], due to an inability to assess E/A.…”
Section: Discussionmentioning
confidence: 99%
“…Waist-to-height ratio has been tested as a surrogate for abdominal obesity in adults and children and seems to be a better predictor of cardiometabolic risk than BMI [56,57]. High sensitivity CRP is a biomarker that quantifies low grade systemic inflammation, in the absence of overt systemic inflammatory or immunologic disorders and has been used as a predictor of cardiovascular events [58], but has been also associated with diastolic dysfunction and heart failure in adults [59][60][61]. In the study of Dahiya et al in obese adolescents, CRP was an independent determinant of LV diastolic function [21].…”
Section: Discussionmentioning
confidence: 99%